Evaluation of the Banking System on the Basis of Expectations and Actual Experiences of the Customers: A Comparison of Islamic and Conventional Banks in Punjab, Pakistan - Sabir, Raja Irfan; Azeem, Bilawal; Nawaz, Farooq (Journal of Asian Business Strategy, 2015)
Purpose of this research is to evaluate the competitiveness of Islamic banks in comparison with conventional banks on the basis of expectations and actual experiences of customers. For this, data had been collected from the customers of Islamic and Conventional banks. An Early Warning System (EWS) has been used to analyze expectations and actual feelings of respondents. Evaluation was carried out on the basis of ten factors selected with the help of literature review i.e. Efficient Employee (EE), Convenience (CO), Customization (CU), Service Process (SP), Value Added Service (VS), Interest Free Service (IS), Online Functional (OF), Sensory Experience (SE), Investment Climate (IC), Technological Change (TC). (a) The research findings describe conventional banks are more competitive than Islamic banks on the bases of ten factors describes above. (b) The Respondents / Users of Conventional banks are highly satisfied however there is need for improvement in Interest Free Service (IS) factor. (c) The Respondents / Users of Islamic banks are almost satisfied regarding factors such as Customization (CU), Service Process (SP), Online Transaction (OT) and Investment Climate (IC) and remaining factors need improvement.